Research Progress on Synthetic Method of Curdlan Composite and Its Application in Food Industry - Xingyan WANG; Wenmei HU; Wei XU; Yuting LI; Tinghong MA; Shan CHEN (Shipin gongye ke-ji)
Curdlan, a triple-helical polysaccharide, produced by microorganisms, is received extensive attention in the food industry owing to its safety and unique chain conformational transformation capability. Compared with other natural triple-helical polysaccharides, curdlan exhibits superior suitability for forming composites due to its abundant hydroxyl groups and unbranched structure. Curdlan-based composite materials constructed using different methods are safe, efficient, and multifunctional food additives, rendering them a hot topic in food research. Herein, the basic structure and features of curdlans are systematically analyzed in this review. Additionally, different synthesis methods for curdlan-based composite materials are described, including physical crosslinking, chemical crosslinking, double-network crosslinking, and self-assembly. Furthermore, relationships between the synthesis methods of curdlan-based composite materials, their structural properties, and applications in the food industry are examined. Finally, the application status of these materials is summarized, existing challenges are presented, and future research directions for their use in the food industry are suggested. This review provides important references and serves as a guide for the applications of curdlan-based composite materials in the food industry.